Comunicação, consumo e ética: as telenovelas da Rede Globo e a construção da virtude moral evangélica - Chioccola, Fabrizzio Saitta (2014)
The continuous growth of the Evangelical churches in Brazil has been contributing to an increasing number of faithful and the space that they occupy on the fabric of the Brazilian society. Such an advance, to some extent, contributes to the fact that this religious group has been spreading its doctrines, with its ethical and moral values, throughout the different levels of our society. This fact can be noticed on the political, economical and social areas. Taking as departing points, the studies on the Theory of Mediations and reception, added by the research on the consuming we propose to study the reception processes of the TV Novels produced by TV Globo by its evangelical audiences. We intend to pursue a theoretical-methodological approach that will take us to a better understanding of such relationship between the Globo TV novels productions and the evangelical audiences. For this reason, we have worked with insights of authors such as Baccega, Chauí, Escosteguy, Hall, Jacks, Kant, Lopes, Marcondes, Martín-Barbero, Motter and Orozco-Gómez. The research takes as corpus the evangelical universe, but at the same time, for the sake of narrowing our study group, we decided to focus on the Pentecostal and neo-Pentecostal segments of the evangelical universe. The method that was used on the empirical study was designed and implemented with the aim of getting closer to the subject of our studies, making it possible to analyze the processes of macro and micro mediation proposed by Orozco-Gómez, and also taking into account both the environment of the Church and the home of these social actors as local mediations between imposition of ethical and moral meanings and practices of reception of Rede Globo TV Novels.